Analysis of factors affecting community compliance with the Covid-19 prevention health protocol in Jambi City Indonesia: SEM-PLS model approach - Anderson, Irzal; Kuswanto, Kuswanto (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
This study aims to determine the pattern of compliance of the people of Jambi City to the Covid-19 prevention health protocol. Various factors that influence the level of community compliance were analysed using the Structural Equation Model (SEM) approach with Partial Least Square (PLS) or SEM-PLS. Data were obtained from the results of a survey of the people of Jambi City who were selected based on regional sampling techniques, starting from the District and Village. Determination of the number of samples using the Slovin formula, the results obtained were 277 respondents. The results of the analysis show that the level of community compliance with the Covid-19 prevention health protocol is quite high. The legal awareness variable significantly mediates the effect of social status variables and legal socialization on legal compliance but is not significant as a mediator of the influence of legal culture variables on legal compliance. For this reason, it is necessary to concern all parties to build public awareness by (1) providing education and understanding through effective socialization programs, (2) building cooperation with community leaders, especially religious leaders and traditional leaders, and (3) providing concessions to the community. Public. So that the poor is not constrained in complying with the Covid-19 prevention health protocol.